The Case for Philosophical Mindedness - Christou, Theodore Michael; Bullock, Shawn Michael (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2012)
This essay is an extended argument for a philosophical disposition with regards to pedagogy, and an argument for all educationists, not merely a select few toiling in the academy, to seek wisdom. Engaged in vocations involving teaching and learning, we must aspire to be wise. Being a philosophically minded educationist means occupying a radical middle between opposing viewpoints and thinking critically, in action, about educational experiences. Far from stereotypical notions linking philosophy to abstract ideals of the ivory tower, we argue that being an educationist and taking this responsibility seriously means being a frontline classical philosopher—one who loves wisdom and who is willing to facilitate the birth of ideas.